Awareness, acceptance, and hesitancy about COVID-19 vaccine among residents of urban and rural health training center field practice area of a medical college at Kolkata: A cross-sectional survey - Sain, Sonali; Chattopadhyay, Amitabha; Haldar, Dibakar (Asian Journal of Medical Sciences, 2023)
Background: Effective vaccination is a successful tool for controlling COVID-19 pandemic, along with other preventive measures. Both intention to get vaccinated and barrier to vaccination played important role in COVID vaccination drive. Aims and Objectives: The present study was conducted to assess awareness, acceptance, and hesitancy about COVID-19 vaccine among the residents of rural and urban area and to assess the factors related to their attitude. Materials and Methods: A descriptive cross-sectional survey was conducted among the adult residents of urban and rural area over 6 months. Total sample size was 400. Simple random sampling technique was adopted to recruit the study participants after obtaining informed verbal consent. This process was continued until the desired number of sample size was attained. Data were compiled after collection and analysis was done. Results: Rural population had significantly higher knowledge of coronavirus and urban population knew prevention of coronavirus infection more. Correct knowledge of COVID vaccine availability was higher among rural people but higher knowledge of vaccine related information was among urban population. Sources of information were mainly from mass media. Vaccine acceptance was more among urban population, but apprehension was significantly higher among urban residents. Higher proportion of urban people was motivated significantly by the healthcare workers as well as self-motivated than their rural counterpart. Conclusion: Targeted interventions could be developed for increasing awareness of disease and availability of COVID-19 vaccines. Population-based vaccination program can decline the trend of the pandemic in long term.